Building Competitive Advantage for Economic Performance: A Study of the Palm Plantation Company in West Kalimantan - Nurmala, Nurmala (International Journal of Economics and Financial Issues, 2018)
The world market for palm oil and its derivative product tend to be increasing. It is an opportunity for Indonesian palm plantation industry especially in West Kalimantan Province in Indonesia to increase its competitive advantage so it will reach optimum economic performance. The increasing competitive advantage has determined by company ability in implementing customer focus, competitor intelligence, and cross functional working relationship. This research has conducted beside to find the model of customer focus, competitor intelligence, and cross functional working relationship implementation at palm plantation company in West Kalimantan Province in Indonesia and also to find the influence of those variables to competitive advantage and company economic performance’s model. This research uses an approach of economic science with the focus on market-based economic. The observation has been conducted to palm plantation company in West Kalimantan Province in Indonesia producing the palm and its derivative products in the forms of CPO and PKO. The research conducted is descriptive and verification using descriptive and explanatory survey method. This research is population research of 85 companies using a data collecting technique of questionnaires equipped with interview and observation. The field data have been collected and the processed using a path analysis.The research result shows that almost all of company in palm plantation industry at West Kalimantan Province in Indonesia has able to implementing customer focus and cross functional working relationship in its business activity. Meanwhile, only half of company in palm plantation industry at West Kalimantan Province in Indonesia able to implementing competitor intelligence and competitive advantage. It’s same with economic performance which only half of company in palm plantation industry at West Kalimantan Province in Indonesia able to achieve high qualification of economic performance. Other outcomes are the competitor intelligence having significant influence on the company’s competitive advantage and competitor intelligence together with the cross functional working relationship having significant influence on the company’s economic performance. Finally, this research found also that the competitive advantage has a significant influence on the company’s economic performance. Keywords: Market-Based Economic, Customer Focus, Competitor Intelligence, Cross Functional Working Relationship, Competitive Advantage, Economic Performance. JEL Classifications: O13, P17, Q47